Komsos Kak's Youtube Content Analysis of Environmental Day Shepherd's Letter in Moving People to Preserve the Environment - Benediktus Tri Widiatmaka; C.B. Mulyatno; Indra Sanjaya Tanureja (CV. Rayyan Dwi Bharata, 2022)
In the midst of various problems of environmental damage, the responsibility to care for the environment is still something that needs to be given a special portion. In addition, the development of communication technology is also increasingly advanced and sophisticated. Youtube as an online platform is a place for catechesis in caring for the environment. The purpose of this research is to find out how the analysis of the youtube content for Social and Social Affairs of the Jakarta Archdiocese (KAJ) in the World Environment Day Shepherd's Greeting series invites people to care for the environment. This research uses content analysis method. The analysis of the content is the delivery of teachings from Cardinal Suharyo in the form of a faith catechesis about caring for the earth. Through his explanatory narration, the Cardinal invites people to take care of the earth as our common home. The results of this study indicate that Cardinal Ignatius Suharyo's greeting in the KAJ Komsos youtube content has become a catechesis for preaching faith to the people in the context of protecting and preserving the environment.